Levels and kinds of explanation: lessons from neuropsychiatry - Wilkinson, Sam (Frontiers in Psychology, 2014)
I use an example from neuropsychiatry, namely delusional misidentification, to show a distinction between levels of explanation and kinds of explanation. Building on a pragmatic view of explanation, different kinds of explanation arise because we have different kinds of explanatory concerns. One important kind of explanatory concern involves asking a certain kind of “why” question. Answering such questions provides a personal explanation, namely, renders intelligible the beliefs and actions of other persons. I use contrasting theories of delusional misidentification to highlight how different facts about the phenomenon that is being explained impose constraints on the availability of personal explanation.